O MOVIMENTO MIGRATÓRIO SAZONAL DOS ATLETAS DE FUTEBOL PROFISSIONAL NA REGIÃO FRONTEIRIÇA BRASIL-BOLÍVIA - Osvaldo Gonçalves Junior (2024)
The main objective of this study was to understand the dynamics of the seasonal migratory movement of professional football players in the Brazil-Bolivia borderregion in Corumbá, a Brazilian city located in the state of Mato Grosso do Sul. Thus, the work addresses the diverse and peculiar characteristics that occur in the study region, especially the migratory flow and the impacts on professional football athletes of Corumbaense Futebol Clube (CFC). The sample included Brazilian footballers over 18 years old who live in Brazil and have played in the city of Corumbá-MS (Brazil) between 2010 and 2021, considering those who had to look for alternative work in amateur teams in Bolivia. Therefore, the seasonality of border football along with the challenges and opportunities of this context, were the central topics articulated for investigation in this research. For this purpose, a descriptive methodology was adopted. Data was collected through empirical research, using a semi-structured interview script, which was recorded by audio recording. The interview scheme was divided into three different blocks of questions, covering: 1) the profile of the professional footballer; 2) the involvement of the professional footballer in the border environment; and 3) the career of the professional footballer and the border context. The final evaluation includes an analysis of the information obtained during the fieldwork, aiming to enrich reflections and debates by integrating theoretical concepts with empirical data, promoting a holistic approach and based on scientific production on the subject to date. Based on the results of the research, some challenges related to the seasonality of CFC athletes in Bolivia were identified. Among these challenges were the poor state of the lawns on the playing fields, the possibility of injuries, and the lack of employment contracts. However, this seasonality has presented considerable opportunities for these athletes, such as complementing the annual football calendar, significant financial gains, maintaining physical and technical condition with a view to an eventual return to professional football, as well as the chance to get closer to and experience a new culture in Bolivia. In conclusion, the results indicate promising paths and reveal some horizons for a better understanding of the issue in the locality studied, as well as suggesting the need for more in-depth studies on seasonal migration in the region. The study also highlights the need to implement public policies and/or private sector initiatives to ensure that CFC athletes remain engaged in paid activities throughout their professional careers. This is especially relevant considering that the Brazil-Bolivia border context, despite its complexity, presents significant opportunities.